Zum Gebrauch der Modalverbform sollte im fachinternen medizinischen Diskurs - Bogusława Rolek (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Modal verbs are characterised by functional flexibility. They are language phenomena that have been in the centre of linguistic attention for years. Yet research on the use of modal verbs in specialised discourse is scarce. The present paper provides the results of the analysis which was devoted to the use of the forms „sollte“ in medical specialised discourse.